2007
DOI: 10.1111/j.1744-697x.2007.00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding value of supplemented diet with black tea by‐product silage: Effect of polyethylene glycol addition to the diet on digestibility of protein fractions in goats

Abstract: The feeding value of black tea by‐product silage was studied both in vitro and in vivo. To estimate the effect of tannins in black tea by‐product on nutrient digestibility, polyethylene glycol (PEG) was also given to goats as a tannin‐binding agent. Regarding in vitro ruminal fermentation, supplementation of black tea by‐products silage to basal substrates at more than 1% on a dry matter (DM) basis decreased the ammonia‐N (NH3‐N) concentration in the medium, indicating that black tea by‐products suppressed pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…Academic Publishers that feeding of black tea grounds at a 5% DM of the total diet to goats showed lower CP digestibility and higher excretion of acid-detergent insoluble proteins; these could be interpreted as tannin-protein complexes (Kondo et al, 2007). In contrast with PPC on a DM basis, two types of barks also showed higher levels of PPC on a TEPH basis among the by-products in the present study.…”
Section: Ne Uscontrasting
confidence: 49%
“…Academic Publishers that feeding of black tea grounds at a 5% DM of the total diet to goats showed lower CP digestibility and higher excretion of acid-detergent insoluble proteins; these could be interpreted as tannin-protein complexes (Kondo et al, 2007). In contrast with PPC on a DM basis, two types of barks also showed higher levels of PPC on a TEPH basis among the by-products in the present study.…”
Section: Ne Uscontrasting
confidence: 49%
“…These results indicate a similarity in the amount of dry matter consumed from the three diets and a marked improvement in feed conversion efficiency of the experimental lambs, especially the third diet, which contains 15% of tea residues of its components compared with other treatments. This is probably due to the decrease in methane production which led to the reduction of the proportion of protozoa inside of the lambs rumen which it were consumed rations was containing tea residues and this in turn contributed to increase the activity of microbial growth at the expense of protozoa inside of the rumen and this was reflected increase in amount of bacterial protein which resulted in utilization protein of tea residue and thus increase the net energy value for maintenance and growth, which affected the amount of energy and protein consumed and leads to increases feed for nutrient compounds and therefore was reflected on growth improved in the third treatment when compared to growth of the first and second treatments (Storry, 1970;Müller 1993;Zinder, 1993;Tokura et al, 1999).These results are consistent with the results of Begum et al (1996) in beef calves, Baruah, 1997, Kondo et al (2004 in milking cows and Müller 1993, Kondo 2007, Singer et al (2008, in fattening of goat who they found no significant effect of tea waste as a nitrogen source in the diet on dry matter intake and food conversion efficiency. These results have been confirmed with results of Wang et al (2011) who found account improvement in feed conversion efficiency when they used tea saponins at levels of 3,6gm/day when as compared with the comparison of goat group.…”
Section: Results and Discussion Performance And Growth Of Lambssupporting
confidence: 84%
“…When they were used different levels (0,0.5,1,2%) of green tea wastes instead of dried brewers grains in fattening rations of pigs. The results are not agreement with the results of Begum et al (1996) in Bangladesh beef calves and Baruah, (1997) in feeding of hybrid milking cows (Assam local × Jersey), Kondo et al (2004) in dairy cows (Holstein) when were fed on experimental rations that had contained (tea waste) and Kondo et al (2007) in fattening of goat who did not find any significant effect when addition tea residues in proportions as a nitrogen source in diet on daily and total weight gains, final weight of ruminant animals. As for statistical analysis of daily feed intake and feed conversion efficiency (Table 2) were not statistical analysis because of feeding group.…”
Section: Results and Discussion Performance And Growth Of Lambsmentioning
confidence: 60%
“…1996), polyethylene glycol (Makkar 2003) and the use of microbial additives (Kondo et al . 2007). Among these methods, the use of microbial additives can be interesting.…”
Section: Introductionmentioning
confidence: 99%